(untitled) (Revista Cocar, 2020)
Este artigo é decorrente de uma pesquisa realizada no âmbito do Programa Institucional de Apoio à Pesquisa da Universidade do Estado de Minas Gerais, no segmento da educação infantil, em uma escola da Rede Privada de Belo Horizonte-MG, com crianças de 3 a 4 anos, em uma turma de Maternal III. Teve como principal objetivo analisar como o brincar, enquanto linguagem essencial e cultura da criança, se configura nas territorialidades infantis constituídas pelas crianças em escolas de educação infantil no município de Belo Horizonte- MG. A pesquisa trouxe à tona a evidência de que as crianças se apropriam dos espaços, atribuindo-lhes outros usos e significados, constituindo territorialidades por meio de um processo de produção de culturas, próprias do mundo delas. Abstract This article is the result of a research carried out under the Institutional Research Support Program of the University of the State of Minas Gerais, in the segment of early childhood education, in a school of the Private Network of Belo Horizonte-MG, with children from 3 to 4 years old, in a Maternal III classroom. Its main objective was to analyze how the playing, as an essential language and culture of the child, is configured in the children’s territorialities constituted by them in schools of early childhood education, in the municipality of Belo Horizonte- MG. The research brought to light the evidence that children appropriate the spaces, giving them other uses and meanings, constituting territorialities through a process of production of cultures, proper of their world.